2015
DOI: 10.1002/2015ja021438
|View full text |Cite
|
Sign up to set email alerts
|

Fringe field dynamics over equatorial and low‐latitude ionosphere: A three‐dimensional perspective

Abstract: This paper presents a three‐dimensional simulation of the collisional interchange instability generating equatorial plasma bubble (EPB) in the evening ionospheric F region and associated fringe field (FF) in the valley‐upper‐E (VE) region. This simulation is primarily intended to address hitherto unexplained radar observations of ascending irregularity structures only in the vicinity of the magnetic equator in association with the EPB phenomenon. Novel results of the present simulation are the following: (1) E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…These features can explain why valley-type irregularities are not observed in the RTI maps from VHF radar observations at low latitudes (Patra and Venkateswara Rao, 2007;Mukherjee and Patra, 2014). Also, Kherani and Patra (2015) explained the electrodynamic origin of the asymmetries noted in the raising structures (Fig. 8) in the E and F valley regions.…”
Section: Langmuir Probe Measurementsmentioning
confidence: 71%
See 2 more Smart Citations
“…These features can explain why valley-type irregularities are not observed in the RTI maps from VHF radar observations at low latitudes (Patra and Venkateswara Rao, 2007;Mukherjee and Patra, 2014). Also, Kherani and Patra (2015) explained the electrodynamic origin of the asymmetries noted in the raising structures (Fig. 8) in the E and F valley regions.…”
Section: Langmuir Probe Measurementsmentioning
confidence: 71%
“…More recently, Kherani and Patra (2015) showed that the fringe field associated with large-scale irregularities penetrates only within the bell of ±5 • from the magnetic equator. These features can explain why valley-type irregularities are not observed in the RTI maps from VHF radar observations at low latitudes (Patra and Venkateswara Rao, 2007;Mukherjee and Patra, 2014).…”
Section: Langmuir Probe Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we employ the two dimensional (longitude-altitude) version of three-dimensional (longitudealtitude-latitude) simulation model of CII/EPB developed by Kherani et al, 13 by fixing latitude ¼ 0 corresponding to the geomagnetic equator. The model solves the following hydromagnetic equations in the ionosphere:…”
Section: Simulation Modelmentioning
confidence: 99%
“…[], Huba and Joyce [, ], Sousasantos et al . [], Kherani and Patra [], and so forth. The amount of information provided by these mathematical approaches increased significantly, although the predictability of the EPBs still continues to be a demand for this field of space physics research.…”
Section: Introductionmentioning
confidence: 99%